Aplicação de ultra-som em hidrólise enzimática de acetatos alquílicos e arílicos: síntese de feromônios - Trindade, Alisson Fagner dos Santos (2006)
This work enlarge the study of the enzymatic hydrolysis mediated by ultrasound primary, secondary and tertiary acetates models. The substrates used in this reactions were: 1-methylpentyl acetate, 1- methylhexyl acetate, 1-methyloctyl acetate, 1,5-dimethyl-4-hexenyl acetate, 1-butyl-2- propenyl acetate, 2-ethyl-hexyl acetate, 1-isobutylpentyl acetate, 1-phenyletyl acetate, ciclohexyl(phenyl)methyl acetate, 1,2,3,4-tetrahydro-1- aphthalenil acetate and 1- methyl-1-(5-methyltetrahydro-2- furanyl)ethyl acetate. Some alcohols prepared by these enzymatic hydrolysis are pheromones (sulcatol, 2-methyl-4-octanol, 1-phenylethanol and 2-(5-methyltetrahydro-2-furanyl)-2-propanol), which can be used in the control of insects. The enzymes valued in these reactions were: pig liver esterase (PLE), Candida rugosa lipase (CRL) and Aspergilus oryzae protease (AOP). In general way, the use of ultrasound bath lead to an appreciative decrease in the reaction time of enzymatic hydrolysis reactions for alkyl and aryl acetates when compared with the use of magnetic stirring in the same reactions, excepting when PLE was used. in enzymatic hydrolysis of the 1-isobutylpentyl acetate